2020
DOI: 10.1001/jamanetworkopen.2020.18141
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Pressure With Cause-Specific Mortality in Mexican Adults

Abstract: IMPORTANCE Elevated blood pressure is a major cause of premature death, but there is little direct evidence demonstrating this association in studies of Hispanic populations. OBJECTIVE To assess the association between blood pressure and cause-specific mortality in a large cohort of Mexican adults with a high prevalence of uncontrolled diabetes. DESIGN, SETTING, AND PARTICIPANTS A total of 159 755 adults aged 35 years or older from 2 districts in Mexico City were recruited to this cohort study between April 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Moreover, it is consistent with data from other studies, including those with robust methodology, from our Region. For example, data from large cohorts from Cuba ( 33 ), Mexico ( 34 ) and South America ( 35 ) confirm the fundamental role of hypertension as the leading cause of CVD events, mortality and trends. Another limitation is the primary data sources for this analysis: GBD study ( 1 ) and NCD-RisC study ( 16 ).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it is consistent with data from other studies, including those with robust methodology, from our Region. For example, data from large cohorts from Cuba ( 33 ), Mexico ( 34 ) and South America ( 35 ) confirm the fundamental role of hypertension as the leading cause of CVD events, mortality and trends. Another limitation is the primary data sources for this analysis: GBD study ( 1 ) and NCD-RisC study ( 16 ).…”
Section: Discussionmentioning
confidence: 96%
“…«артериальная гипертензия ассоциируется с повышенным риском смерти от сердечно-Южно-Российский журнал терапевтической практики South Russian Journal of Therapeutic Practice 2022;3(2):63-70 сосудистых осложнений и прогрессирующим нарушением функции почек» -заключение, которое в настоящее время рассматривается как постулат, не требующий дополнительных доказательств [9]. по данным китайских ученых, наблюдавшим в течение 9 лет более 500 тысяч пациентов в возрасте от 30 до 79 лет, повышение ад на каждые 10 мм рт.…”
Section: Discussionunclassified
“…In Mexico City, a large cohort study in people aged 35 years and older showed that previously diagnosed diabetes at baseline was associated with about four times the death rate from cardiovascular disease relative to adults without diabetes (41). These results were ratified in a resurvey assessment of this cohort carried out between 2015 and 2019 that concluded that the excess mortality associated with high systolic blood pressure was substantially greater among individuals with diabetes, especially those with poorly controlled diabetes (42).…”
Section: Cardiovascular Diseases and Diabetesmentioning
confidence: 95%